Controlling Dense Layers of Pawpaw (Asimina triloba) in Mesic Upland Forest Understories. Issue 3 (27th March 2018) - Olson, Matthew G; Keeley, Michael T
Abstract: Pawpaw ( Asimina triloba ), a shade-tolerant shrub native to eastern North America, sometimes forms a dense layer in forest understories that may interfere with tree regeneration. The purpose of this study was to evaluate silvicultural methods for controlling dense understory layers of pawpaw. In 2013, a study was initiated to test three pawpaw control options in southeastern Missouri: prescribed fire, broadcast foliar herbicide, and prescribed fire followed by spot foliar herbicide. All manipulative treatments caused an immediate reduction in pawpaw cover. Decreases in control were evident by the second year. For pawpaw cover < 3 feet, control in year two decreased the most in treatments that included fire (i.e., fire-only and fire + herbicide), while control of pawpaw cover ≥ 3 feet declined in the fire-only treatment, but remained high in treatments that included herbicide (i.e., herbicide-only and fire + herbicide). These results suggest treatments that include herbicide will provide greater immediate control of dense pawpaw layers than sole use of a single prescribed fire. However, the large reduction in pawpaw cover observed immediately following a single burn suggests that pawpaw layers may not form in stands subjected to repeated burning.